PENGARUH KOMUNIKASI, EFEKTIVITAS KEPEMIMPINAN DAN KONDISI KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN LABUHANBATU - Hasibuan, Desmawaty (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
This study aims to analyze the influence of communication, effectiveness and working conditions on employee job satisfaction at the office of the ministry of religion in the district of Labuan. The data collection method in this research is questionnaire, interview, documentation and observation. The sampling technique used is probability sampling technique. The population that became the object of this study were employees of the South Kuala sub-district office with a sample of 32 employees. Hypothesis testing is done by multiple linear regression analysis through the SPSS 20.0 for windows program. Based on the results of the research with a significance level of 5%, it is concluded that the tcount for the Communication variable is 3.294, the Leadership Effectiveness is 2.051 and the Working Conditions is 7.015. Based on the criteria that if the value of tcount> ttable); namely (3,294> 1,701, (2,051> 1,701), (7,015> 1,701) so it can be concluded that partially the communication variable has a positive and significant effect on job satisfaction, leadership effectiveness has a positive and significant effect on job satisfaction and working conditions has no positive effect and significant to the job satisfaction of employees at the Office of the Ministry of Religion Labuhanbatu district.